MIF-mediated NF-κB signaling pathway regulates the pathogenesis of polycystic ovary syndrome in rats. (October 2021) - He, Zhenlin; Wang, Yuelong; Zhuan, Li; Li, Yunxiu; Tang, Z-ouyin; Wu, Ze; Ma, Yanping
Highlights: Testosterone promoted the increase in the levels of MIF and LH but inhibited the increase in the level of FSH. The MIF antibody could alleviate the process of PCOS to a certain extent. Testosterone propionate promoted the expression of IL-1β, IL-6, iNOS, and TNF-α; the MIF antibody could reverse this effect. Testosterone promoted the expression of NF-κB protein in the nucleus; this effect also could be reversed by the MIF antibody. Abstract: Polycystic ovary syndrome (PCOS) resulting from abnormal glucose metabolism is a relatively common and complex endocrine disorder among women in their reproductive years, However, the pathogenesis of PCOS is still unclear. The purpose of this study is to investigate the macrophage migration inhibitory factor (MIF) involvement of the nuclear factor (NF)-κB in rats with PCOS. Results indicated that testosterone promoted the increase in the levels of MIF and luteinizing hormone (LH) but inhibited the increase in the level of follicular stimulating hormone (FSH). The MIF antibody could alleviate the process of PCOS to a certain extent. Testosterone promoted the expression of interleukin 1-beta (IL-1β), interleukin 6 (IL-6), Inducible nitric oxide synthase (iNOS), and tumor necrosis factor alpha (TNF-α); the MIF antibody could reverse this effect. Testosterone could inhibit the expression of NF-κB protein whereas MIF antibody could promote the expression in the ovarian cytoplasm. Testosterone promoted the expression of NF-κB protein in the nucleus, this effect also could be reversed by the MIF antibody. Hyperandrogenism activated the NF-κB pathway. After using the MIF antibody, this effect was reversed. This finding suggested that hyperandrogenism activated the NF-κB pathway through MIF. In short, increased MIF levels activated the NF-κB pathway in ovaries, leading to inflammation and the increase in the levels of relevant inflammatory indicators, which might be one of the important factors in the pathogenesis of PCOS.